The High-Stakes Balance: Patient Safety and Neurosurgical Practice in a COVID-19 Pandemic - Sumardi, Fitri Sepviyanti (Jurnal Neuroanestesi Indonesia, 2025)
Introduction: The COVID-19 pandemic profoundly affected neurosurgical practices globally, prompting the introduction of emergency health protocols to safeguard patients and healthcare personnel. While these measures were essential for controlling virus spread, they were resulted in challenges like surgical delays, resource shortages, and heightened stress for medical staff. This study aims to evaluate the impact of these protocols on neurosurgical care, identify the challenges posed, and suggest strategies to enhance patient safety and healthcare resilience in future outbreaksSubject and Methods: This qualitative study involved a systematic literature review on PubMed, Google Scholar, and ScienceDirect, along with interviews with neurosurgeons, anesthesiologists, and intensive care specialists. Through thematic analysis, it explored the disruptions in neurosurgical care during the pandemic, the adaptive strategies employed, and their impact on patient outcomes and medical staff well-being.Results: The study found that while emergency health protocols helped minimize COVID-19 transmission, they caused significant disruptions in neurosurgical care, with 30% of patients experiencing delays that adversely affected their outcomes. PPE shortages, inconsistent preoperative screening, and changing health protocols complicated surgical workflows. Hospitals with structured triage systems, expanded telemedicine, and enhanced preoperative screening managed the crisis better. Additionally, healthcare workers' psychological distress was reduced through improved mental health support and resource availability.Conclusion: The COVID-19 pandemic has transformed neurosurgical practice, highlighting the need for adaptation and resilience in healthcare. Strengthening collaboration, optimizing resources, and integrating technology will better prepare neurosurgical teams for future public health emergencies while maintaining high-quality patient care.